Environmental Factors Associated with Pneumonia in Children Under-Five in Nduga District, Papua - Yulianda Yeimo; Isna Qadrijati; Bhisma Murti (Masters Program in Public Health, 2018)
Background: Pneumonia is an inflammatory condition of the lung affecting primarily the small air sacs known as alveoli. In 2016 UNICEF had reported that pneumonia remains the leading infectious cause of death among children under five, killing approximately 2,400 children a day. Mortality due to childhood pneumonia is strongly associated to poverty, lack of safe water and sanitation, indoor air pollution and absence of basic immunization. This study aimed to determine the environmental factors associated with pneumonia in children under-five in Nduga, Papua, Indonesia. Subjects and Method: This was an analytic observational study with case-control design. This study was conducted in Yigi and Mbua Sub-districts, Nduga District, Papua, Indonesia, from December 2017 to February 2018. A sample of 184 children under-five consisting of 88 children with pneumonia (case) and 96 children without pneumonia (control), was selected for this study by fixed disease sampling. The independent variables were BCG immunization status, family income, indoor household air pollution, and environmental sanitation. The dependent variable was pneumonia. Data were collected by questionnaire and medical record. The data were analyzed by a multiple logistic regression.Results: The risk of pneumonia in children under-five increased by absence of BCG immunization (OR= 6.15; 95% CI= 2.78 to 13.61; p< 0.001), poor indoor household air pollution (OR= 5.68; 95% CI= 2.63 to 12.26; p< 0.001), and poor sanitation (OR= 5.06; 95% CI= 2.16 to 11.83; p<0.001). The risk of pneumonia in children under-five decreased by higher family income (OR= 0.30; 95% CI= 0.13 to 0.70; p= 0.005).Conclusion: Pneumonia in children under five is associated with indoor household air pollution, poor sanitation, absence BCG immunization, and lower family income.Keywords: pneumonia, indoor pollution, sanitation, BCG immunization, family incomeCorrespondence: